1969
DOI: 10.1139/f69-171
|View full text |Cite
|
Sign up to set email alerts
|

Maturity and Fecundity of Walleyes from the Eastern and Western Basins of Lake Erie

Abstract: Of 2427 walleyes (Stizostedion vitreum vitreum (Mitchill)) examined from Lake Erie in 1964–66, no females were mature at ages below III and all were mature at age V. All male walleyes from the eastern basin were mature at age II, and those from the western basin at age III. Females from the western basin matured at a shorter length and a younger age than those from the eastern basin. Males from the western basin, on the other hand, matured at a longer length and greater age than those from the eastern basin.Eg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

1975
1975
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 1 publication
4
23
0
Order By: Relevance
“…5). For example, specific fecundity for older maturing walleyes from Lake of the Woods was 15 (data from Carlander 1945) and 144 for the faster growing and earlier maturing walleyes in the western basin of Lake Erie (data from Wolfert 1969). Both values are within the range hypothesized in Fig.…”
Section: Although Planted Walleyes Have Been In Casa Blancasupporting
confidence: 59%
See 1 more Smart Citation
“…5). For example, specific fecundity for older maturing walleyes from Lake of the Woods was 15 (data from Carlander 1945) and 144 for the faster growing and earlier maturing walleyes in the western basin of Lake Erie (data from Wolfert 1969). Both values are within the range hypothesized in Fig.…”
Section: Although Planted Walleyes Have Been In Casa Blancasupporting
confidence: 59%
“…There is some evidence that younger fish, many immature, do not travel as great a distance as the older members of the stock (Wolfert 1963;Priegel 1970;Winterton 1975). WoIfert ( 1963) found in Lake Erie that more walleyes tended to travel greater distances as their ages increased, and Priegel (1970) found in both the Fox and Wolf rivers in Wisconsin that younger age-groups sf walleyes did not migrate as far upstream as did older age-groups.…”
Section: Although Planted Walleyes Have Been In Casa Blancamentioning
confidence: 99%
“…Body Wolfert 1969Wolfert , 1977 Walleye 213 371 454 513 563 607 649 683 722 760 Hile 1954 Walleye 163 305 414 480 541 582 617 645 668 Priegel 1969 Walleye 152 257 338 394 439 480 511 536 Eschmeyer 1950 Walleye 125 239 315 368 414 455 480 503 518 533 Smith and Pycha 1961 Walleye 142 211 267 310 345 379 401 424 452 Note: All body lengths are total body length. Table A1.…”
Section: Appendix Amentioning
confidence: 99%
“…Individual females normally spawn in one night (Ellis and Giles 1965). The number of eggs produced and released is linearly related to body size within a population and averages 60 OOO/kg (Stickney 1986), but ranges from 28000 to 120000/kg between populations (Smith 1941;Wolfert 1969). O'Donnell(l938) observed that 200-300 eggs were released during each spawning act, with the acts repeated at 5-min intervals.…”
Section: Reproductive Biologymentioning
confidence: 99%